Multifunctional monomer acts as co-initiator and crosslinker to provide autonomous strengthening with enhanced hydrolytic stability in dental adhesives. Issue 2 (February 2020) - Song, Linyong; Sarikaya, Rizacan; Ye, Qiang; Misra, Anil; Tamerler, Candan; Spencer, Paulette
Graphical abstract: Highlights: ASMA monomer serves multiple roles, i.e. acts simultaneously as co-initiator and co-monomer and provides self-strengthening. ASMA-containing adhesive shows a substantial reduction of leached of HEMA and BisGMA. Simulation-based on Prony-series-fitting provides information about the self-strengthening phenomenon. Abstract: Objective: The purpose of this study was to evaluate a new synthesized multifunctional monomer, aminosilane functionalized methacrylate (ASMA), containing polymerizable methacrylate, tertiary amine, and methoxysilane functionalities in dental adhesive formulations, and to investigate the polymerization kinetics, leachates, thermal and mechanical properties of copolymers. Methods: Adhesive contained HEMA/BisGMA (45/55, w/w) was used as a control, and mixtures based on HEMA/BisGMA/ASMA at the mass ratio of 45/(55-x)/x were used as experimental adhesive. Adhesives were characterized with regard to water miscibility, photo-polymerization behavior (Fourier transform infrared spectroscopy, FTIR), leached co-monomers (high performance liquid chromatography, HPLC), thermal properties (modulated differential scanning calorimeter, MDSC), and mechanical properties (dynamic mechanical analyzer, DMA). Stress relaxation times and the corresponding moduli, obtained from stress relaxation tests, are used in a simulated linear loading case. Results: As compared to the control, ASMA-containing adhesives showed higher water miscibility, lower viscosity, improved monomer-to-polymer conversion, significantly greater Tg and rubbery modulus. HPLC results indicated a substantial reduction of leached HEMA (up to 85 wt%) and BisGMA (up to 55 wt%) in ethanol. The simulation reveals that the ASMA-containing adhesive becomes substantially stiffer than the control. Significance: ASMA monomer plays multiple roles, i.e. it serves as both a co-initiator and crosslinker while also providing autonomous strengthening and enhanced hydrolytic stability in the adhesive formulations. This multifunctional monomer offers significant promise for improving the durability of the adhesive at the composite/tooth interface.